العلاقات القطرية - الإسرائيلية (1995 – 2008) - , م.م. خالد رزاق مالح (Thi Qar Arts Journal, 2021)
The beginnings of the Qatari approach to normalization with Israel can be traced back to the Madrid Peace Conference in the Middle East in 1991, and the subsequent meetings between the two parties after that date. With Sheikh Hamad bin Khalifa Al Thani assuming the reins of power in Qatar on June 27, 1995, a major change occurred in the constants of foreign policy. Qatar, through Sheikh Hamad bin Khalifa’s tendency to get out of Saudi Arabia’s domination of Qatar’s political decision, was keen to adopt new political mechanisms to achieve these goals, including closer relations with the United States of America on the one hand and accelerating the pace of normalization and cooperation with Israel on the other hand. Qatar entered into a state of political hypocrisy towards Arab and Islamic countries in most of the stations of its relationship with Israel. Qatar apparently tended to announce criticism of Israel while it carried out any aggression it carried out against the Palestinians and the Lebanese, and in secret it was moving towards expanding its relations with the Israeli side. In order to preserve its own interests.The Qatari-Israeli relations during the period discussed in the research ranged between ups and downs according to the political and security situation in the region. Both sides were keen to continue strengthening those relations, but the surrounding pressures that each party was subjected to is what prevented this relationship from being on a single pace. The features are clear to everyone, especially the Qatari side, which has often faced internal, Arab and Islamic refusal to stop normalization with Israel, whose aggressive and provocative policies in the region were behind those pressures directed on the Qatari side.